Lucky me : a memoir of changing the odds - Paul, Rich, 1981-; Washington, Jesse, 1969- (Roc Lit 101, 2023)
"Rich Paul grew up in a Cleveland that hadn't won a sports championship in decades. He and his siblings lived with their mother, who struggled with addiction, in a one-bedroom apartment in the poverty-stricken Glenville neighborhood. Young Rich dreamed of becoming a star athlete but realized quickly that his small stature would make it nearly impossible. A serious child with a mind for detail, he went to private school and then college at his shop-owner father's encouragement. But he quit when his father died of cancer, devoting himself to becoming the family's next entrepreneur. Paul began selling vintage jerseys out of the trunk of his car, and during one stint at the Akron-Canton Airport, a seventeen-year-old NBA prospect complimented the Warren Moon jersey that Rich was wearing. They struck up a friendship and exchanged contact information. By the next year, LeBron James signed with the Cleveland Cavaliers, and Rich Paul was working alongside him. Paul was finally in the big leagues, but the industry wasn't necessarily ready to accept him. With grit, passion, and an unwavering sense of self, Paul forged a new path, and the NBA hasn't been the same since. Lucky Me is the memoir of that extraordinary journey told in Paul's blunt, philosophical style, but it is also so much more. It is a book full of inspiration and insight, and a testament to never compromising who you are for anyone"--